2017
DOI: 10.1097/sla.0000000000002098
|View full text |Cite
|
Sign up to set email alerts
|

Prophylactic Negative Pressure Dressing Use in Closed Laparotomy Wounds Following Abdominal Operations

Abstract: Prophylactic use of negative pressure dressings for closed laparotomy wounds significantly reduces the incidence of SSI at 30 days postoperatively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
113
1
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(120 citation statements)
references
References 25 publications
3
113
1
3
Order By: Relevance
“…The LOS was reported in eight studies representing 725 patients [ 28 , 29 , 31 , 36 , 39–41 ]. There was a significant mean difference in LOS from PICO single-use NPWT treatment compared with standard care (−0.47 days [95% CI −0.71 to −0.23] p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The LOS was reported in eight studies representing 725 patients [ 28 , 29 , 31 , 36 , 39–41 ]. There was a significant mean difference in LOS from PICO single-use NPWT treatment compared with standard care (−0.47 days [95% CI −0.71 to −0.23] p < 0.0001).…”
Section: Resultsmentioning
confidence: 99%
“…The detail of each individual study and the overall data and subgroup analysis (as a forest plot) is shown in Figure 5 . A subgroup analysis was performed on the basis of surgical speciality, and mean difference in LOS was −5.1 days in colorectal/laparotomy surgical procedures [ 39–41 ] but only −0.1 days in all other operations [ 28 , 29 , 31 , 36 , 40 ].…”
Section: Resultsmentioning
confidence: 99%
“…Numerous trials and meta-analyses have confirmed a benefit of NPWT in adult patients who underwent abdominal surgery. 13.5% in contaminated, and 14.6% in dirty/infected wounds. 18 Bhattacharyya and Kosloske studied prospectively 676 consecutive patients and found an overall infection rate of 2.5% ranging from 1.0% in clean wounds, 2.9% in clean-contaminated, 7.9% in contaminated, and 6.3% in dirty wounds.…”
Section: Discussionmentioning
confidence: 94%
“…stay 13. NPWT has been successfully used in orthopedic,14 cardiothoracic,15 and abdominal16 closed surgical incisions.…”
mentioning
confidence: 99%
“…A total of 35 articles discussed prophylactic VSD (pVSD) for abdominal incisions with primary suture, of which 6 were RCTs 32 , 33 , 34 , 35 , 36 , 37 and 29 were observational studies. 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 , 62 , 63 , 64 , 65 , 66 …”
Section: Recommendationsmentioning
confidence: 99%